Internet use in the home: Digital inequality from a domestication perspective - Scheerder, Anique J; van Deursen, Alexander JAM; van Dijk, Jan AGM (New media & society, 2019)
This study uses a domestication approach to digital inequality. The aim is to uncover whether and why less-educated families benefit less from Internet use than highly educated families. The predominantly quantitative approach of digital divide research provides little explanation as to why digital inequalities exist. Interviews were conducted with the heads of 48 Dutch families. The results showed that Internet use and routines in the home are shaped differently for families with different educational backgrounds. In all four phases of domestication, the highly educated demonstrated a critical view toward the Internet, resulting in considered use and redefinition. Less-educated members tended to be less interested in Internet developments and overall have a less reflective stance. Inequalities between different social strata already arise in the early stages of domestication and are magnified in the subsequent phases.